The potential beneficial effect of sleep deprivation following traumatic events to preventing PTSD: Review of current insight regarding sleep, memory, and trauma resonating with ancient rituals—Àìsùn Oku (African) and Tsuya (Japanese). Issue 1 (9th January 2023) - Cohen, Hagit; Ephraim‐Oluwanuga, Olusola T.; Akintunde, Orunmuyi T.; Gureje, Oye; Matar, Michael A.; Todder, Doron; Zohar, Joseph
Abstract: Sleep figures in numerous ancient texts, for example, Epic of Gilgamesh, and has been a focus for countless mystical and philosophical texts. Even in the present century, sleep remains one of the most complex behaviors whose function still remains to be further explored. Current hypotheses suggest that among other functions, sleep contributes to memory processes. Memory is a core topic of study in post‐traumatic stress disorder (PTSD) and other stress‐related phenomena. It is widely accepted that sleep plays a major role in the consolidation of newly encoded hippocampus‐dependent memories to pre‐existing knowledge networks. Conversely, sleep deprivation disrupts consolidation and impairs memory retrieval. Along this line, sleep deprivation following a potentially traumatic event may interfere with the consolidation of event‐related memories and, thereby, may reduce long‐term post‐traumatic stress‐related symptoms. This review consolidates clinical and animal studies on the relationships between sleep, sleep deprivation, memory processes, and trauma exposure while introducing new contemporary insights into an ancient African tribal ritual (Àìsùn Oku) and Japanese ceremony ritual (Tsuya). We propose that these findings, focusing specifically on the effects of sleep deprivation in the immediate aftermath of traumatic events, may be explored as a possible therapeutic measure. Along with a summary of the field questions on whether sleep is performed "to remember" or "to forget" we lay the rationale for using sleep deprivation as a clinical tool. A tool that may partially prevent the long‐term persistence of these traumatic events' memory and thereby, at least partly, attenuating the development of PTSD. Abstract : Memory formation is associated with initial encoding to establish a short‐term memory (STM) followed by a time dependent consolidation phase to establish a stable long‐term memory (LTM). Once a memory is a long‐term memory its remains fixed or permanent. The results of this review suggest that prevention of sleep in the early aftermath of stress exposure may be beneficial in attenuating traumatic, stress‐related sequelae. Post‐exposure SD impairs hippocampus‐dependent traumatic memory formation and consolidation, a mechanism possibly pertinent to the development of PTSD.